Green Consumerism - Issues and Implications - Santhi, P.; Jerinabi, U.; Gandhi, N. Mohandas (Indian Journal of Marketing, 2007)
It is now widely accepted that societies, economies and the businesses within them need to find a more sustainable path for future development. Achieving this will involve saying some very new things about marketing and perhaps rediscovering some of the fundamental truths. Marketing has contributed to the current environmental crisis, because of its central role as a driving force behind the unsustainable growth in consumption or what could be termed over consumption. Marketing as it will become, by contrast, will become part of the solution. This will require the marketing of new, more sustainable produced products, new companies, new life styles, new values and new ideas."Green" is a term coined in Europe to refer to a particular politics and lifestyle; green consumerism involves making consumption decisions based on environmental concerns; implies a rejection of wasteful consumption. Green consumerism (or socially conscious consumerism) can be described as the use of individual consumer power to promote less environmentally damaging consumption, while still satisfying consumer wants and needs. Green consumerism means a great deal more than simply changing over from an earth-bashing product to a slightly more environmentally sensitive one. It means questioning both, the nature and volume of consumption.